INVESTIGATING THE USE OF MULTIMODALITY IN EFL CLASSROOM AT INDONESIAN UNIVERSITY NON-ENGLISH DEPARTMENT - Halim Halim; Nukmatus Syahria; Nunung Nurjati (Universitas Wiralodra, 2025)
This study aims to investigate private university students' views on multimodality approach in EFL class. There is still a lot of traditional EFL teaching approach that are not as good at matching different learning styles and capturing students' attention. A multimodality approach provides creative solutions. The participants in this study were 21 non-English department students consisting of eight male students and thirteen female students. The research design examines students' experiences and perceptions of multimodality in the classroom using a qualitative approach and a narrative inquiry method. Reflection and in-depth interviews were used to gather data. Key themes in the participants' experiences were found by applying thematic analysis approaches to the data. The findings show that the multimodality approach helps students' understanding of English language material and helps optimize student engagement. From the students' perspective, there are four main themes, namely an interactive and motivating learning environment, a fun and enjoyable learning environment, diverse learning styles, and self-confidence growth. Further research can explore the effectiveness of multimodal approaches quantitatively to measure the improvement of students’ learning outcomes more objectively. In addition, further studies can involve more participants from various university backgrounds and study programs to expand the generalizability of the findings.